Motor learning and performance - Schmidt, R. A.; Wrisberg, C. A. (Human Kinetics, 2008)
The student-friendly fourth edition of Motor Learning and Performance: A Situation-Based Learning Approach expands on the fundamentals of motor performance and learning, providing valuable supporting literature and current research results in an accessible and engaging format. This text goes beyond simply presenting the latest research. Instead, Schmidt and Wrisberg challenge students not only to grasp but also to apply the fundamental concepts of motor performance and learning via a unique situation-based approach. Movement practitioners using this approach continually ask three basic questions to assist people in motor learning: who (the person learning or performing), where (the context for learning or performing), and what (the task being learned or performed). By working through situation-based exercises and case studies, students learn how to ask appropriate questions, identify solutions, and support their answers with theory or research.Motor Learning and Performance: A Situation-Based Learning Approach outlines the principles of motor skill learning, develops a conceptual model of human performance, and shows students how to apply the concepts of motor learning and performance to a variety of real-world settings, including teaching, coaching, the design of performer-friendly equipment and work environments, rehabilitation, and everyday motor skill learning. Straightforward explanations of motor skill concepts and accompanying research are reinforced with both ordinary and extraordinary examples of motor skill activities, such as driving a car, playing the banjo, and mountain climbing. By applying the concepts of motor learning to familiar scenarios, the material comes alive for students, leading to better retention of information and greater interest in the application of motor performance and learning in their everyday lives and future careers.More than 76 new references, exercises, updated figures and photos, and improved chapter features make the fourth edition of Motor Learning and Performance: A Situation-Based Learning Approachthe most user-friendly edition to date. Each chapter is organized to include an outline listing the major topics to be presented, objectives that alert students to key content for mastery, an opening case study that previews the content within the context of a real-life example, research highlight boxes to provide more detailed descriptions of important experiments and concepts, and a running glossary for instant definitions of terms as they are introduced in the text. In addition, the authors make the text even more reader friendly with these elements:-It Depends sections require students to identify factors that might influence motor performance and learning situations.-From Principles to Practice sections simplify self-testing of key terms by reviewing and providing exercises to apply the information to real-life situations.-Special notes with interesting facts and quotes provide supplemental information.-A summary with a compilation of important concepts wraps up each chapter.-Four additional in-depth case studies are featured in the final chapter. New and convenient online instructor resources are also available to course adopters of this updated text. The ancillary materials include an expanded instructor guide with chapter summary notes and additional situation-based exercises for class discussion, a presentation package of PowerPoint slides for lectures, and a test bank.Motor Learning and Performance: A Situation-Based Learning Approach, Fourth Edition, continues to combine a conceptual model of human performance with a situation-based learning approach, making comprehension of the principles of motor performance and learning accessible even for readers with little or no knowl